A Lenda da Carioca e o mito de origem da mulher vilaboense - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
In the city of Goiás, the oral tradition constitutes an important repository of narratives that are part of the imaginary and of the vilaboense people. However, historiography still does not register many of them, fact that leads to the proposal of this research whose objective is to study the origin of the myth and the legend, as well as to identify the written versions of this legend in the work of the goiana female poets. The research comprehends the indigenous woman as a character of the legendary narrative, and, in this sense, carries out the study on vilaboense woman from the origin indigenous. The archetypes that shape the narratives are characterized, so as to focus on the historical, individual and collective identity of the female figure present in the Carioca legend, in its different versions and in other legends, its legacy for the formation of vilaboense women. The research has as theoretical corpus a qualitative / quantitative approach, adopting the methodology of bibliographical research and surveys that use different theories about myth, memory, culture and literature as an instrument of analysis of the narratives collected from the researched sources.
Keywords: Mito de origem; Lenda da Carioca; Mulher vilaboense; Myth of origin; Legend of Carioca; Vilabian woman; LINGUISTICA, LETRAS E ARTES